2022
DOI: 10.3389/fendo.2022.917113
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Muscular Atrophy: Molecular Mechanisms and Promising Therapies

Abstract: Diabetes mellitus (DM) is a typical chronic disease that can be divided into 2 types, dependent on insulin deficiency or insulin resistance. Incidences of diabetic complications gradually increase as the disease progresses. Studies in diabetes complications have mostly focused on kidney and cardiovascular diseases, as well as neuropathy. However, DM can also cause skeletal muscle atrophy. Diabetic muscular atrophy is an unrecognized diabetic complication that can lead to quadriplegia in severe cases, seriously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 118 publications
(136 reference statements)
2
37
0
Order By: Relevance
“…1,2 Skeletal muscle plays an indispensable role in overall health as the primary organ of postprandial insulin stimulated glucose uptake and a significant contributor to whole body metabolic rate. Metabolic perturbations impact muscle mass, 3 suggesting that strategies targeting mitochondrial metabolism could be an effective way to mitigate or reverse obesity 4 including sarcopenic obesity, 5 type 2 diabetes induced muscle atrophy, 3 and cancer cachexia mitochondrial dysfunction. 6,7 Exercise is a prime intervention that improves muscle metabolic health in disease 8,9 ; however, vigorous exercise may not be possible in all patients due to their existing comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Skeletal muscle plays an indispensable role in overall health as the primary organ of postprandial insulin stimulated glucose uptake and a significant contributor to whole body metabolic rate. Metabolic perturbations impact muscle mass, 3 suggesting that strategies targeting mitochondrial metabolism could be an effective way to mitigate or reverse obesity 4 including sarcopenic obesity, 5 type 2 diabetes induced muscle atrophy, 3 and cancer cachexia mitochondrial dysfunction. 6,7 Exercise is a prime intervention that improves muscle metabolic health in disease 8,9 ; however, vigorous exercise may not be possible in all patients due to their existing comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…[32] . Muscle wasting can occur as a result of metabolic imbalances such as starvation, weightlessness, or diabetes [33,34] . These imbalances disrupt protein anabolism and catabolism, leading to secondary muscle loss [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T2DM or obesity are prone to muscle atrophy, which has a detrimental effect on their daily activities and quality of life and may shorten their life expectancy 81 . Imbalance in protein synthesis and degradation is the underlying cause of muscle atrophy, and obesity and long‐term nutritional excess are associated with insulin resistance and chronic inflammation, ultimately impeding the growth of muscle fibres 82 . Recent studies have identified three proteins belonging to the TRIM family that impact myofibre growth or differentiation: TRIM32 and TRIM72 regulate muscle differentiation by controlling the PI3K subunit p85 and IRS‐1‐AKT signalling pathways, while TRIM63 may contribute to myasthenia gravis by increasing oxidative stress and muscle catabolism.…”
Section: Mechanisms Of Trim Proteins In Diabetes and Its Complicationsmentioning
confidence: 99%